(untitled) (Italiano LinguaDue, 2017)
L’educazione plurilingue e interculturale risponde alla necessità e alle esigenze di un’istruzione di qualità: acquisizione di competenze, conoscenze e atteggiamenti, diversità di esperienze di apprendimento e costruzione di identità culturali individuali e collettive. Si tratta di rendere i sistemi educativi più efficaci e di migliorare il loro contributo al successo scolastico degli studenti più vulnerabili e alla coesione sociale. Questa guida vuole essere uno strumento per una migliore attuazione dei valori e dei principi dell’educazione plurilingue e interculturale nell’insegnamento di tutte le lingue: straniere, regionali, minoritarie, lingue classiche e lingua (e) di scolarizzazione. Guide for the development and implementation of curricula for plurilingual and intercultural education Plurilingual and intercultural education is a response to the needs and requirements of quality education, covering the acquisition of competences, knowledge and attitudes, diversity of learning experiences, and construction of individual and collective cultural identities. Its aim is to make teaching more effective and increase the contribution it makes both to school success for the most vulnerable learners and to social cohesion. This guide is intended to facilitate improved implementation of the values and principles of plurilingual and intercultural education in the teaching of all languages – foreign, regional or minority, classical and language(s) of schooling.